Dietary milk fat globule membrane supplementation during late gestation increased the growth of neonatal piglets by improving their plasma parameters, intestinal barriers, and fecal microbiota. Issue 29 (30th April 2020) - Zhang, Xiangyu; Wu, Yujun; Ye, Hao; Feng, Cuiping; Han, Dandan; Tao, Shiyu; Pi, Yu; Zhao, Junying; Chen, Lijun; Wang, Junjun
Abstract : Maternal supplementation of MFGM transgenerationally improves the intestinal microecology and growth performance of their neonatal piglets. Abstract : Milk fat globule membrane (MFGM), mainly comprising protein and fat, has been reported to have multiple biological functions for relieving intestinal inflammation and enhancing growth performance. We hypothesized that MFGM supplementation into sows' diet during late gestation can have a positive impact on the intestinal microecology of sows and their piglets, as well as on the growth of neonates. Therefore, the present study was conducted to investigate such effects and their potential mechanisms. Twenty-two pregnant sows were selected and randomly divided into the CON group (basal diet) and MFGM group (basal diet supplemented with 9.9 g per day MFGM). The feeding period began from d 85 of gestation and until farrowing. The concentrations of albumin (ALB), low-density lipoprotein cholesterol (LDL-C), and non-esterified fatty acids (NEFA) in plasma and short-chain fatty acids (SCFAs) in feces of sows from the MFGM group were determined. The concentrations of growth hormone (GH), immunoglobulin A (IgA), glucose (GLU), and NEFA in the umbilical cord blood in the MFGM group were significantly higher than those in the CON group. Piglets from the MFGM group showed improved growth performance, increased villus height in the jejunum, decreased crypt depth in the duodenum and jejunum, upregulated mRNA expressions of tight junctions (namely, Occludin; Claudin-1, Claudin-2, and Claudin-4; zonulin-1 (ZO-1)); mucins such as Mucin 2, Mucin 4, Mucin 13, and Mucin 20; and immune-related genes, such as tumor necrosis factor-α (TNF-α), interferon-γ (INF-γ), interleukin-22 (IL-22), toll-like receptor 2 (TLR2), and toll-like receptor 4 (TLR4). In addition, the abundance of Prevotella in the feces of sows at farrowing and the abundance of Christensenellaceae_R-7_group in the feces of 21 day-old piglets from the MFGM group were significantly higher. Further correlation analysis revealed that the Christensenellaceae_R-7_group was positively correlated with the relative mRNA expressions of Occludin, Claudin-1, Claudin-2, Claudin-4, Mucin 13, TLR2, and TLR4. In conclusion, MFGM supplementation during late gestation improved the physiological status of sows by improving their plasma parameters and intestinal microecology. The improved provision of nutrients through the umbilical cord blood and optimized microbiota colonization in neonatal piglets were beneficial to the intestinal morphological structure and barrier functions, consequently improving the growth performance of neonates during lactation. These findings provide insights into the future applications of MFGM with regard to maternal–fetal nutrition and a new option for nutritional intervention of neonates through maternal dietary manipulation.